Development and validation of the RapidHIT™ 200 utilising NGMSElect™ Express for the processing of buccal swabs. (August 2018) - Shackleton, David; Pagram, Jenny; Ives, Lesley; Vanhinsbergh, Des
Highlights: Development of RapidHIT™ 200, using NGMSElect™, for single source buccal samples. Development of DNA typing system that processes samples in under 2 h. Validation to ISO17025 of process including a RapidHIT™ 200 device for single source buccal samples. Application of RapidHIT™ 200 device to UK criminal justice system. Abstract: The RapidHIT™ 200 System is a fully automated sample-to-DNA profile system designed to produce high quality DNA profiles within 2 h. The use of RapidHIT™ 200 System within the United Kingdom Criminal Justice System (UKCJS) has required extensive development and validation of methods with a focus on AmpFℓSTR ® NGMSElect™ Express PCR kit to comply with specific regulations for loading to the UK National DNA Database (NDNAD). These studies have been carried out using single source reference samples to simulate live reference samples taken from arrestees and victims for elimination. The studies have shown that the system is capable of generating high quality profile and has achieved the accreditations necessary to load to the NDNAD; a first for the UK.